Functional differences between the long terminal repeat transcriptional promoters of human immunodeficiency virus type 1 subtypes A through G - Jeeninga, R E; Hoogenkamp, M; Armand-Ugon, M; de Baar, M; Verhoef, K; Berkhout, B (Journal of virology, 2000)
The current human immunodeficiency virus type 1 (HIV-1) shows an increasing number of distinct viral subtypes, as well as viruses that are recombinants of at least two subtypes. Although no biological differences have been described so far for viruses that belong to different subtypes, there is considerable sequence variation between the different HIV-1 subtypes. The HIV-1 long terminal repeat (LTR) encodes the transcriptional promoter, and the LTR of subtypes A through G was cloned and analyzed to test if there are subtype-specific differences in gene expression. Sequence analysis demonstrated a unique LTR enhancer-promoter configuration for each subtype. Transcription assays with luciferase reporter constructs showed that all subtype LTRs are functional promoters with a low basal transcriptional activity and a high activity in the presence of the viral Tat transcriptional activator protein. All subtype LTRs responded equally well to the Tat trans activator protein of subtype B. This result suggests that there are no major differences in the mechanism of Tat-mediated trans activation among the subtypes. Nevertheless, subtype-specific differences in the activity of the basal LTR promoter were measured in different cell types. Furthermore, we measured a differential response to tumor necrosis factor alpha treatment, and the induction level correlated with the number of NF-kappaB sites in the respective LTRs, which varies from one (subtype E) to three (subtype C). In general, subtype E was found to encode the most potent LTR, and we therefore inserted the core promoter elements of subtype E in the infectious molecular clone of the LAI isolate (subtype B). This recombinant LAI-E virus exhibited a profound replication advantage compared with the original LAI virus in the SupT1 T-cell line, indicating that subtle differences in LTR promoter activity can have a significant impact on viral replication kinetics. These results suggest that there may be considerable biological differences among the HIV-1 subtypes.